Conjunto de herramientas basadas en resolución de conflictos y relajación para el manejo de conductas agresivas que inciden en la convivencia escolar (2022)
The purpose of this research project was to determine the effects of a set of tools for the management of aggressive behavior in students of a public school located in the city of Bogota, Kennedy, about school coexistence. Using a quasi-experimental design with a non-probabilistic and homogeneous sampling. The population consisted of 38 students from sixth grade and 9 teachers who teach these students; using a pretest and posttest which was applied through a structured interview, since it is one of the techniques of the quantitative method for data collection (Borda, 2011). The findings obtained show a reduction of aggressive behaviors in students, since they learned what they are and how to identify them, reflecting on the effects that can generate the practice of this type of behavior in someone, in addition, when they are exposed to conflict situations they have conflict resolution strategies that allow them to give a better response to such situations. In order to elaborate the theoretical basis of this research, aggressive behaviors within the school environment were defined by authors such as Levinson and Marín, relaxation defined by Prado and Charaf, the mindfulness technique explained by Kabat-Zinn, conflict resolution from the perspective of Álzate and assertive communication described by Llacuna, Pujol and Rodríguez.